(untitled) (International Journal of Biomedical Research, 2015)
The regulation of the peroxisome proliferator-activated receptor (PPAR) isoforms in macrophages by cytokines is of potentially crucial importance in the pathogenesis of atherosclerosis. However, the precise mechanisms by which different cytokines modulate the expression of macrophage PPAR isoforms activity are still poorly understood. In the present study, we evaluated the action of four cytokines on the expression of PPAR isoforms mRNA, protein and functional PPAR-DNA binding activity in the murine macrophage J774.2 cell line, a widely used model system for atherosclerosis. Exposure of the cells to tumour necrosis factor alpha (TNF?) and interferon gamma (IFN?) for 24h, produced a dose-dependent reduction of PPAR alpha and gamma isoforms (PPAR? and PPAR?) and a dose-dependent increase of the PPAR beta/delta isoforms (PPAR?/?) mRNA and protein expression. In contrast, interleukin-1 beta (IL-1?) produced a dose-dependent increase of PPAR? and PPAR? and a dose-dependent decrease in PPAR?/? mRNA and protein expression. However, IL-1? has no effect on all isoforms of PPAR mRNA and protein expression. Electrophoretic mobility shift assay (EMSA) showed a close correlation between the expression of the PPAR mRNA, protein and the functional PPAR-DNA binding activity. Incubation of nuclear extracts with anti-PPAR antibodies in super-shift assay demonstrated the participation of all the three PPAR isoforms in the binding to the peroxisome proliferator response elements (PPRE). These results indicate that TNF?, IFN?, IL-1? and IL-1? are important regulators of macrophage PPAR gene and protein expression which affect its DNA binding activities. Thus, this study provides novel insights into the potential mechanisms that may be responsible for the mediator specific regulation of macrophage gene expression through the PPAR isoforms, indicating a possible physiological and potential role for this transcription factor in modulating arterial lipid metabolism and inflammatory response associated with atherosclerosis.